2019
DOI: 10.1038/s41598-018-35773-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences Associated With Circulating PCSK9 in Patients Presenting With Acute Myocardial Infarction

Abstract: A limited number of studies have explored whether the role of circulating proprotein convertase subtilisin/kexin type 9 (PCSK9) in the pathogenesis of acute myocardial infarction (AMI) is sex specific. The purpose of the present study was to examine sex differences in plasma PCSK9 in Chinese patients with AMI. In this study, a total of 281 records from patients presenting with AMI were analyzed.We compared hospital data and plasma PCSK9 levels by sex difference for inpatients presenting with AMI. After 1 year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
4
15
1
2
Order By: Relevance
“…It was worth mentioning that, we did not find the association between PCSK9 and some indictors, mainly HDL-C, TG and their derived indexes in DM patients, which may be due to the higher heterogeneous in metabolic phenotypes. In addition, the present study showed that patients with high plasma PCSK9 concentration were more likely to be female, which was consistent with previous studies [37,38]. The reason for this phenomenon may be that plasma PCSK9 levels are influenced by hormones such as estrogen [39].…”
Section: Discussionsupporting
confidence: 92%
“…It was worth mentioning that, we did not find the association between PCSK9 and some indictors, mainly HDL-C, TG and their derived indexes in DM patients, which may be due to the higher heterogeneous in metabolic phenotypes. In addition, the present study showed that patients with high plasma PCSK9 concentration were more likely to be female, which was consistent with previous studies [37,38]. The reason for this phenomenon may be that plasma PCSK9 levels are influenced by hormones such as estrogen [39].…”
Section: Discussionsupporting
confidence: 92%
“…Regardless of the absolute plasma concentrations of PCSK9, our findings are in line with most previous reports showing that PCSK9 varies with sex, with the exception of two studies that find no gender difference in small cohorts [22,23]. Indeed, we found that PCSK9 plasma concentration was higher in women than in men, in both the univariate and the multivariable analysis, and this result is in agreement with studies in large, ethnically diverse, general populations [7,18,24], in a large population-based sample of children and adolescents [25], and in diverse cohorts of patients with stable coronary artery disease (CAD) or ACS [26,27].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the modifiable risk factors of AMI in our study should be able to achieve a fair degree of control; however, women's long‐term and CV mortality is 20%‐30% higher than those of men, which should not only be blamed on unmodifiable risk factors such as age. Zhang et al found that the concentration of PCSK9 in women with MI was relatively high than that in men, although the PCSK9 concentration itself was not significantly associated with MI prognosis in their study 22 . In the future, more studies are required to investigate the underlying physiological changes in women with AMI.…”
Section: Discussionmentioning
confidence: 68%
“…Zhang et al found that the concentration of PCSK9 in women with MI was relatively high than that in men, although the PCSK9 concentration itself was not significantly associated with MI prognosis in their study. 22 In the future, more studies are required to investigate the underlying physiological changes in women with AMI. In addition, the literature indicates that women have poorer medication adherence after MI than men, 23 and similar findings have been reported in the medical treatment of hyperlipidemia 24 and diabetes mellitus.…”
Section: Characteristicsmentioning
confidence: 99%